Effect of Foot SPA in Improving Touch Perception in Patients with Type 2 Diabetes - Ruslan Hasani; Gede Wiadnyana; Bahtiar Bahtiar; Junaidi Junaidi; Rahman Rahman; Sri Angriani; Sukriyadi Sukriyadi; Hamsina Hamsina (Jurnal Penelitian Pendidikan IPA, 2023)
Amputation of lower limbs and the development of foot ulcers are primarily associated with Diabetes Mellitus (DM) and its associated sensory peripheral neuropathy (SPN). A diminished perception of touch perception leads to decreased responsiveness to pressure and is recognized as a risk factor for diabetic foot ulcers. Increasing SPN patients' sense of touch perception in their feet may help prevent foot ulcers. This study aimed to prove the effects of foot SPA in improving touch perception in patients with type 2 Diabetes. This research method is quasi-experimental with one group pre and post-test design without a control group. Sampling was done by purposive sampling with 22 research subjects. The research instrument used a 10-g monofilament test. Foot SPA is carried out 6 days for week. Data analysis used the Paired sample t-test. Statistical test results obtain a p-value <0.05. The results of a week-long study found that foot SPA significantly affects touch perception in type 2 diabetes patients.